Permissivism, the value of rationality, and a convergence‐theoretic epistemology. - Ye, Ru (Philosophy & Phenomenological Research, 2023)
The article focuses on permissivism, the value of rationality, and a convergence-theoretic epistemology. Topics include the debate between impermissivists and permissivists regarding whether there can be multiple rational responses to the same evidence; and the response to the value problem by introducing a convergence-theoretic approach to rationality and arguing that it is compatible with permissive.